Comparison of macroinvertebrate assemblages across a gradient of flow permanence in an agricultural watershed. (12th September 2017) - Smith, C.R.; McCormick, P.V.; Covich, A.P.; Golladay, S.W.
Abstract: In the south‐eastern United States and globally, increasing human water demand coupled with climate change is diminishing stream flows and increasing stream intermittency in many watersheds. We characterized benthic invertebrate assemblages across a stream flow gradient ranging from intermittent to perennial following a multiyear drought by examining the functional traits that can influence assemblage response to drying. We sampled 13 reaches within the Lower Flint River Basin in south‐western Georgia, from September to December 2013. Reaches included perennial, near‐perennial (ceased flowing but maintained a wetted channel during drought), intermittent‐dry (seasonally dry), and intermittent‐frequent (frequently dry). Distinct assemblages were documented across this gradient. Reaches that dried during the drought had a lower richness of aquatic insects, especially Ephemeroptera, Plecoptera, and Trichoptera taxa, partly due to inadequate time for life cycle completion and lack of adaptations to avoid drying. Intermittent reaches also included abundant and unique noninsect taxa such as Gammarus spp . and Isopoda. Projected trends towards increased water demand and drought severity and frequency in the south‐eastern United States will magnify shifts towards dominance by drought‐tolerant taxa as greater portions of stream networks become intermittent.